Overhaul and Erection Maintenance Optimization for GuangzhouMetro B-type High-speed Urban Transit Train - ZHAO Wei-long; CHEN Zhi-hong (机车电传动)
Because of the speed characteristics of B-type high-speed urban transit train, overhaul and erection maintenance period of thetrain could not match planned operation mileage well. According to the operation situation of B-type high-speed urban transit train inGuangzhou metro line 3 north-extending line and combined system and components life length impact factors, train components was classifiedand analyzed, and overhaul and erection maintenance optimized project based on components reliability for B-type high-speed urban transittrain was put out, which had been implemented successfully.